Nitrated apolipoprotein AI/apolipoprotein AI ratio is increased in diabetic patients with coronary artery disease. (February 2016) - Chen, Xueying; Bakillah, Ahmed; Zhou, Liye; Pan, Xiaoyue; Hoepfner, Florian; Jacob, Marrit; Jiang, Xian-Cheng; Lazar, Jason; Schlitt, Axel; Hussain, M.Mahmood
Abstract: Aims/hypothesis: Recent studies have suggested that determination of HDL function may be more informative than its concentration in predicting its protective role in coronary artery disease (CAD). Apolipoprotein AI (apoAI), the major protein of HDL, is nitrosylated in vivo to nitrated apoAI (NT-apoAI) that might cause dysfunction. We hypothesized that NT-apoAI/apoAI ratio might be associated with diabetes mellitus (DM) in CAD patients. Methods: We measured plasma NT-apoAI and apoAI levels in 777 patients with coronary artery disease (CAD) by ELISA. Further, we measured plasma cholesterol efflux potential in subjects with similar apoAI but different NT-apoAI levels. Results: We found that median NT-apoAI/apoAI ratio was significantly higher in diabetes mellitus (DM) (n = 327) versus non-diabetic patients (n = 450). Further analysis indicated that DM, thiobarbituric acid-reactive substances and C-reactive protein levels were independent predictors of higher NT-apoAI/apoAI ratio. There was negative correlation between NT-apoAI/apoAI and use of anti-platelet and lipid lowering drugs. The cholesterol efflux capacity of plasma from 67 individuals with differing NT-apoAI but similar apoAI levels from macrophages in vitro was negatively correlated with NT-apoAI/apoAI ratio. Conclusions: Higher NT-apoAI/apoAI ratio is significantly associated with DM in this relatively large German cohort with CAD and may contribute to associated complications by reducing cholesterol efflux capacity. Highlights: There are significant amounts of nitrated apoAI in the plasma of coronary artery disease patients. NT-apoAI/apoAI ratio is significantly higher in diabetes versus non-diabetic patients. This ratio is negatively correlated with macrophage cholesterol efflux independent of apoAI.